Emergency Online Teaching-Learning Model in the Context of Higher-Level Education due to the COVID-19 Pandemic - Hossain, Md. Alamgir; Yasmin, Farhana (Goodwood Publishing, 2022)
Purpose: The study aims at determining a new and complete picture of the ongoing online teaching-learning model based on the university student’s perception of online learning and university teachers’ experiences with their online teaching. Methodology: This study followed a mixed-method approach where both qualitative and quantitative methods are applied. In total 335 university students of both males and females are selected randomly using a questionnaire through Google format. Results: Online platform is the best option to save students from collapsing the academic world in the pandemic situation and so this study developed a new teaching and learning model analysing the practical situation of respondents. It is the main result of it. Limitations: We started this research in 2021 during the horrible COVID-19. Due to which we could not go to the field and collect the data, we have collected the data through the online platform. These are the major limitations of the study. Contribution: However, we mentioned a model for maintaining a graduate-level educational system if any kind of pandemic will come in the future.